Mathematical Modeling and Validation on a New Valve Core of the Throttle Valve in MPD. (18th September 2013) - Fu, Y. K.; Liu, Q. Y.; Wang, G. R.; Tao, S. Y.
Abstract : To achieve different demands for pressure control in managed pressure drilling (MPD), the relationship between the pressure difference and the valve opening was analyzed in the working process of MPD throttle. The throttle flow area equation and the flow area isosurface equation at different openings were derived. Then, the mathematical model of the throttle valve surface shape was established by solving the envelope curve of isosurface cluster. Furthermore, the shape curve equation of the valve core surface was derived and modified by applying this mathematical model. Finally, to verify the performance of this investigation, the comparison of the results between simulation and design values was performed. The results showed that the correlation between the throttle pressure difference and the valve opening is linearly related, which proves the correctness of the mathematical model for the throttle valve surface.